2012
DOI: 10.1080/15313220.2012.704245
|View full text |Cite
|
Sign up to set email alerts
|

Is This for Real? Authentic Learning for the Challenging Events Environment

Abstract: This article explores a set of emerging competencies that education providers will be increasingly compelled to consider, and more importantly, embed in their event management course offerings. The undergraduate event management program offered at Victoria University, Melbourne, provides a case study of the efforts of teaching staff to iteratively and reflectively integrate these emerging competencies into course curriculum, many of which will be required for graduates to successfully transition to work in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…Transformational epiphanies, which emerged through reflection, are learning curves that totally transform the way individuals view the world, themselves as members of society, and the way they think. This was encouraging for module tutors as reflection is what changes a mere experience into a learning exercise (Robertson et al, 2012). As shown in Table 3 the transformational epiphanies are manifested as skills and aptitudes discovered by students through reflection.…”
Section: Student Experiences With the Vocational Degreementioning
confidence: 77%
See 1 more Smart Citation
“…Transformational epiphanies, which emerged through reflection, are learning curves that totally transform the way individuals view the world, themselves as members of society, and the way they think. This was encouraging for module tutors as reflection is what changes a mere experience into a learning exercise (Robertson et al, 2012). As shown in Table 3 the transformational epiphanies are manifested as skills and aptitudes discovered by students through reflection.…”
Section: Student Experiences With the Vocational Degreementioning
confidence: 77%
“…Seminal author Kolb's (1984) model of experiential learning suggested that experience with subsequent reflection enables students to better apply classroom theory to industry practice. Several studies have reported on the positive outcomes of placements, internships, and other forms of workbased learning inside professional organizations for event, hospitality, and tourism students (Beattie, Nixon & Walker, 2008;Fletcher-Brown, Knibbs, & Middleton, 2015;Fox & Morrison, 2010;Hingley, 2008;Nixon & Dray, 2010;Robertson, Junek, & Lockstone-Binney, 2012;Sealy, 2012). Employers place significant value on vocational experience with project management, working with audiences and customers, hands-on production experience, budgeting, fundraising, and marketing planning being highly desirable (Beaven & Wright, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Below I share two insights related to these questions, generated from a review of the educational literature , from explorations of young people's (ages [16][17][18][19][20][21][22][23][24] use of the social network sites MySpace and Facebook in situ (Greenhow and Robelia, 2009a, b;Greenhow and Burton, n.d.;Greenhow et al, 2009), and an ongoing investigation of older adolescents' use of an open source social networking application, implemented within Facebook, and designed for informal science learning and civic action (Greenhow, n.d., 2010). Moreover, I suggest how each theme might inform the design of technology-mediated spaces for learning and questions we might ask in studying such spaces that would move us closer to understanding these questions above.…”
Section: Two Themes: Social Network Sites and Learningmentioning
confidence: 99%
“…Adaptability in an increasingly complex and changeable market is a core requirement of event organization (Robertson et al 2012), and is significant element in sustainable development and practice . However, while scenario planning is already being used in public sector thinking, and indicates recognition of preparedness and adaptability, it may not always be used appropriately.…”
Section: Scenario Planning and Vignettesmentioning
confidence: 99%